THE ROLE OF SUPINE SLEEPING AS A FAMILY-BASED EARLY INTERVENTION FOR SPASTICITY IN CEREBRAL PALSY - Suryani, Ajeng; Susetyo, Budi; Rochyadi, Endang; Tarsidi, Iding; Hasan, Herlina; Qurrotul Uyun, Hana (JPI (Jurnal Pendidikan Inklusi), 2025)
This study aims to explore the application of the supine sleeping position as a form of family-based early intervention to reduce spasticity in children with severe cerebral palsy (CP). The research was driven by limited access to professional therapy services, especially among low-income families. A qualitative approach with a case study design was used. Data were collected through in-depth interviews with parents, observation of sleeping position practices, and family documentation over two months of intervention. The findings show that the family consistently implemented the supine sleeping position using simple household materials. Parents reported improvements in the child's sleep comfort, reduced morning muscle stiffness, and easier daily care routines. Despite challenges such as shifting sleep positions, uncomfortable room temperature, and caregiver fatigue, the family demonstrated adaptive and reflective capabilities. This study concludes that home-based simple interventions like the supine sleeping position have the potential to strengthen the family’s role in supporting independent care for children with severe CP.